UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE COURSE REVIEW HORAY (CRH) - Juitaning Mustika (Universitas Muhammadiyah Pringsewu, 2016)
The students' low achievement in math is due to lack of activities in learning process. Therefore, it needs the effort to increase the students' activity and achievement. One of the way to overcome this problem is using cooperative learning type course review horay (CRH). This study research is a class room action research which aims to: (1) increase the math learning activities in VIII A of SMPN 1 Trimurjo after following the cooperative learning model type CRH; (2) to increase the math achievement of VIIIA of SMPN 1 Trimurjo after following cooperative learning model type CRH. This research was conducted in SMPN 1 Trimurjo. This class room action research was designed in several stages such as planning, action, observation, and reflection of the next stage. This research conducted in two cycles. The research finding is cooperative learning model type, CRH can increase the math learning activities and students' achievement in math of VIIIA SMPN 1 Trimurjo in the main topic of circle. Keywords: course review horay learning model, learning activity, learning outcomes